Pemanfaatan Lusi dan Fly Ash Sebagai Material Bautan Berdasarkan Nilai Berat Jenis Agregat Halus dan Porositas - Toni Budi Santoso (Civil Infrastructure Engineering and Architectural Design, 2023)
Sidoarjo mudflow (Lusi) still occurs today, various efforts to stop and reduce the eruption have been made but have not stop able to stop the Sidoarjo mud. To help reduce the mud being ejected, it is necessary to utilize Sidoarjo mud. Researchers aim to reduce the mud caused by Sidoarjo mud by utilizing artificial materials as substitutes for natural materials. Utilization is also carried out for fly ash which is waste from the PLTU. Sidoarjo mud and fly ash are combined with an alkaline activator to form geopolymer paste and cement paste. The geopolymer paste specimen were tested for specific gravity of fine aggregate and its porosity. The result show Sidoarjo mud has a specific gravity of fine aggregate of 2.519 and fly ash of 2.525 which is greater than specific gracity of water, namely 1. The porosity of the geopolymer paste is 3% and that of cement paste is 3.8%.